Značilnosti obremenitev gibal pri odbojki - Sattler, Tine (Šport (Ljubljana), 2016)
We have described a vertical jump and arm swing as two basic movement patterns in volleyball. Basic functional anatomy is represented for each movement and a relationship between specific loads and injuries in volleyball is explained as an important starting point for the design of training and preventive measures in volleyball.
Keywords: arm swing; injury; obremenitve; odbojka; poškodbe; sport; šport; vertical jumps; vertikalni skok; volleyball; zamah z roko